Southern Decadence in New Orleans - Smith, Howard Philips; Perez, Frank, 1968- (Book collections on Project MUSE., 2018)
"Founded in the summer of 1972 by a few friends as a modest celebration, the Southern Decadence festival has since grown into one of New Orleans's largest annual tourist events. The multiday extravaganza features street parties, drag contests, dancing, drinking, and bead tosses, culminating with a boisterous parade through the French Quarter ... [This book] brings together an ... array of materials to provide the first comprehensive, historical look at [the festival]"--Dust jacket flap.